PENGARUH KOMPENSASI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SELULER MEDIA INFOTAMA BANDA ACEH - Vilzati Juned; Rolly Oka Putra; Samsul Ikhbar (ITB AAS INDONESIA, 2022)
The purpose of this study was to determine the simultaneous effect of compensation and job characteristics on employee job satisfaction at PT. Cellular Media Infotama Banda Aceh, and to determine the effect of compensation on employee job satisfaction at PT. Cellular Media Infotama Banda Aceh, and to determine the effect of job characteristics on employee job satisfaction at PT. Mobile Media Infotama Banda Aceh. This research was conducted at PT. Cellular Media Infotama on Jalan T. Nyak Arief No. 45, Jeulingke Banda Aceh. Data collection techniques through the distribution of questionnaires. The population in this study are employees of PT. Cellular Media Infotama Banda Aceh totaling 90 people and sampling was carried out by census so that the final sample was 90 people or included the entire population in the study as research samples. Data analysis used qualitative and quantitative methods. To find out how big the relationship between compensation and job characteristics with employee job satisfaction, the Multiple Linear Regression tool is used. The results of the study based on the results of the F-test (simultaneous) showed that the variables of compensation and job characteristics had a significant effect on increasing employee job satisfaction at PT. Cellular Media Infotama with a value of Fcount > Ftable, at a significance level of = 5%. The results of the partial study of compensation have an effect on increasing employee job satisfaction at PT. Mobile Media Infotama. While the results of research partially on the variable job characteristics affect the increase in job satisfaction of employees at PT. Mobile Media Infotama. The results of the study also prove that the greater the compensation given to employees, the more job satisfaction of employees at PT. Mobile Media Infotama.